Functional DSCT assessment of tricuspid regurgitation: AROA reproducibility and comparison with 3D TEE. (8th February 2021) - Cunha Lopes, B; Hashimoto, G; Fukui, M; Du, Y; Bae, R; Stanberry, L; S Schwartz, R; R Lesser, J; Sorajja, P; L Cavalcante, J
Abstract: Funding Acknowledgements: Type of funding sources: None. onbehalf: Minneapolis Heart Institute Foundation Background: Tricuspid regurgitation (TR) assessment by echocardiography is often challenging. Functional dual-source CT (DSCT) with third-generation scanners allows accurate evaluation of leaflet anatomy and mobility. Purpose: Investigate the reproducibility of tricuspid anatomical regurgitant orifice area (AROA) by DSCT, and its correlation with TR quantification by 3D TEE. Methods: We evaluated patients with symptomatic TR referred for transcatheter tricuspid repair. DSCT (SOMATOM Force [Siemens, Erlangen, Germany]) and 3D TEE was performed on the same day as part of our institutional registry. DSCT scans were retrospective and ECG-gated, with a contrast protocol to enhance the right heart. The reproducibility of tricuspid AROA was assessed in 20 patients. The tricuspid AROA was compared with the TR severity (5-grade classification) and the 3D VCA by TEE (Panel 1). Results: We included 60 patients (Table). The AROA had excellent intra and interobserver reliability (ICC 0.99 [0.97, 0.99] and 0.99 [0.96, 0.99]). We found a stepwise increase in tricuspid AROA from moderate to torrential TR (Panel 2A). Of 60 patients, 3D VCA was feasible in 39; in those, we found an excellent linear correlation of AROA and 3D VCA (Panel 2B). Conclusions: Tricuspid AROA by DSCT was reproducible, showed a stepwise increase from moderate to massive TR and correlated with 3D VCA by TEE.